Evaluating the potential of relapse-free survival as a surrogate for overall survival in the adjuvant therapy of melanoma with checkpoint inhibitors. (September 2020) - Coart, Elisabeth; Suciu, Stefan; Squifflet, Pierre; Saad, Everardo D.; Moshyk, Andriy; de Schaetzen, Gaetan; Buyse, Marc; Weber, Jeffrey S.; Eggermont, Alexander; Kotapati, Srividya
Abstract: Introduction: Recent changes in the adjuvant treatment of melanoma have raised interest in confirming relapse-free survival (RFS) as a surrogate for overall survival (OS). Methods: We explore this issue with the meta-analytic framework, using individual patient data from the European Organisation for Research and Treatment of Cancer (EORTC) 18071 trial of ipilimumab and published results from other adjuvant trials. Results: The individual patient data analysis results at a median follow-up of 5.3 years showed a strong association between RFS and OS at the patient level (ρ = 0.84; 95% confidence interval [CI]: 0.82–0.87) and a moderate association at the trial level (R 2  = 0.59; 95% CI: 0.08–1.00). Conclusions: The trial-level association previously observed in interferon-based trials appeared to be maintained when the EORTC 18071 results were added to a regression analysis using published results from other trials. More data from adjuvant trials are required to confirm the strength of association between RFS and OS in this setting. Highlights: We explored relapse-free survival (RFS) as a surrogate for overall survival (OS). We used data from the European Organisation for Research and Treatment of Cancer 18071 trial and published results from other trials. We found a strong association between RFS and OS at the patient level. We found a moderate association between RFS and OS at the trial level. Our results are promising and require confirmation with a larger number of trials.